PENGARUH INTERAKSI ANTARA BAP DAN IAA TERHADAP MULTIPLIKASI TUNAS TALAS SATOIMO (Colocasia esculenta (L.) Schott var. antiquorum) SECARA IN VITRO - Muhammad Ilham; Sugiyono Sugiyono; Lucky Prayoga (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2019)
Satoimo (Colocasia esculenta (L.) Schott var. antiquorum) is a type of taro with small tuber size (small corm taro) and called Japanesse taro or satoimo. The conventional method of satoimo propagation takes relatively long time, therefore propagation techniques of satoimo shoot in vitro can be an alternative method to meet the increasing need of satoimo seed. The objectives of research were to study the interaction effect BAP and IAA on multiplication of satoimo shoot as well as to determine the best concentrations of BAP and IAA for satoimo shoot multiplication. This research has been conducted experimentaly using a Completely Randomised Design (CRD) with a factorial treatment pattern. The first factor was BAP concentration (B) with 4 levels i.e B1 : 5 µM, B2 : 7,5 µM, B3 : 10 µM and B4 : 12,5 µM. The second factor was IAA concentrations (I) with 4 levels i.e I1 : 1 µM, I2 : 2 µM, I3 : 3 µM and I4 : 4 µM. The combination of these two factors resulted in 16 treatment combinations. Each combinations repeated 3 times, there were 48 experimental units. The variables observed were taro shoot growth with parameters measured included the number of shoot, leaf and root produced. The data obtained were analyzed using Analysis of Variance (ANOVA) at a 95% level of confidence, followed by a Least Significant Difference (LSD) Test at 5% error rate. The research results showed that the interaction betweem BAP and IAA stimulated shoot and root formation during multiplication of satoimo shoot in in vitro culture. The addition of 5 µM BAP and 2 µM IAA resulted in the best multiplication rate of shoot satoimoin in vitro culture.